FINDING MEANING IN THE TWILIGHT YEARS: AN EXISTENTIAL ANALYSIS OF THE FATHER (2020) AND A MAN CALLED OTTO (2022) - Asih Ernawati; Aurora Magenta Diva (Universitas Muhammadiyah Makassar, 2026)
Existential themes have long shaped cinematic storytelling. However, the intersection of aging masculinity and philosophical inquiry remains underexplored in contemporary film studies. This article investigates the existential dimensions of aging in The Father (2020) and A Man Called Otto (2022). This present study is urgent as most existing research treats aging as a mere biological decline which fails to address the inner philosophical struggles of older male protagonists. Using a qualitative interpretive and comparative design grounded in the existential frameworks of Jean-Paul Sartre and Viktor Frankl, the analysis follows Avci and Cetin’s (2022) three-stage process: data selection, thematic coding, and theoretical interpretation. Four key themes emerge: identity, mortality, isolation, and meaning. The Findings reveal that while The Father (2020) embodies existential dissolution through cognitive decay, A Man Called Otto (2022) depicts a trajectory of rediscovery through community compassion. This study contributes to an interdisciplinary understanding of aging, demonstrating that cinema serves as a vital medium for reframing later as a dynamic existential condition rather a state of passive decline.